Effect of bentonite slurry injection on pipe jacking forces - Namlı, Mücahit. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Pipe jacking is a technique used to form tunnels by pushing prefabricated pipes through the ground from an entrance shaft to an exit shaft. The main limitation for pipe jacking method is limitation of jacking distance. Main aim of this study is trying to advance both the knowledge of the lubricity mechanism at the pipe-soil interface and the technology for lubrication and overcut stability in pipe jacking, in order to upgrade jacking distance by ensuring that lubricants are properly and effectively used, in other words optimization of bentonite injections that is applied for lubrication. For this purpose a research program is started which have laboratory and field stages. Jacking force data of three cases are recorded at the field stage, and at Bogazici University Geotechnical Laboratory, two new laboratory test setups are prepared. At the first laboratory test set up, by applying a constant pressure on 5 cm height bentonite slurry which was poured on sand layer, bentonite slurry injection in pipe jacking operations at the jobsite is tried to be simulated. At the second laboratory test set up by pulling out a concrete pipe sample from sand in condition with and without bentonite slurry around the concrete pipe sample, bentonite slurry injection methods which are commonly used in practice for lubrication are tried to be modeled in laboratory. Interface coefficient of friction results which are obtained from both laboratory tests and field jacking data are evaluated together. As an important result it was determined that with an efficient lubrication, 87% reduction of interface coefficient of friction can be achieved which means 20% reduction of total cost. For this bentonite slurry injection should be done under a constant injection pressure with continuous feeding of bentonite slurry in a pressure closed system. At the end of this study a renovation of bentonite injection system for pipe jacking is recommended.
Keywords: Bentonite slurry.